Ultrasonic Measurement of Body Fat as a Means of Assessing Body Condition in Free-Ranging Raccoons (Procyon lotor). (19th October 2010) - Stringer, Elizabeth M.; Stoskopf, Michael K.; Simons, Theodore; O'Connell, Allan F.; Waldstein, Arielle
Abstract : Assessment of body condition of free-ranging animals is important when evaluating population health and fitness. The following study used body condition scoring, ultrasound, and dissected physical measurement to assess fat stores in free-ranging raccoons ( Procyon lotor ). Measurements were taken of subcutaneous fat at interscapular, thoracolumbar, and lumbosacral paraspinal and ventral midline sites. These measurements were examined in relationship to body condition scores and body weight. The ultrasound technique accurately measured the subcutaneous fat of raccoons when compared to dissected physical measurement and yielded data that strongly correlated with both body condition score and body weight, with the ventral midline measurement most strongly correlated. This noninvasive method may be useful in conjunction with body condition score and body weight when assessing the nutritional status of raccoons and potentially other small carnivore species.